2008
DOI: 10.1016/j.vetmic.2007.11.039
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of immunosuppression in rabbits after infection with myxoma virus

Abstract: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
24
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 29 publications
(33 reference statements)
3
24
0
Order By: Relevance
“…Watzinger et al (2011) reported the increase in CR protein levels observed after injection of antigens (Complete Freund's Adjuvant, typhoid vaccine, saline solutions) to rabbits, what is in contrast with our study with MXT vaccination. On the other hand our results are in agreement with the literature, in which myxoma virus has shown an inherent ability to infect and cause immunosuppression in rabbits after infection (Jeklova et al 2008;Spiesschaert et al 2011). *P < 0.05, **P < 0.01, ***P < 0.001…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Watzinger et al (2011) reported the increase in CR protein levels observed after injection of antigens (Complete Freund's Adjuvant, typhoid vaccine, saline solutions) to rabbits, what is in contrast with our study with MXT vaccination. On the other hand our results are in agreement with the literature, in which myxoma virus has shown an inherent ability to infect and cause immunosuppression in rabbits after infection (Jeklova et al 2008;Spiesschaert et al 2011). *P < 0.05, **P < 0.01, ***P < 0.001…”
Section: Discussionsupporting
confidence: 93%
“…The decrease in the percentage of CD4 + cells after vaccination in our results are in agreement with an earlier study focused on a characterisation of immunosuppression in rabbits after infection with myxoma virus (Jeklova et al 2008) and also with in vitro studies of malignant rabbit fibroma virus (Strayer et al 1987;Strayer 1992). This leporipoxvirus, a hybrid of myxoma virus and rabbit fibroma virus, replicates preferentially in mature T lymphocytes of the spleen but is able to grow in B lymphocytes as well.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…There are two features that are important in the development of generalized lethal disease. Firstly, the replication of myxoma virus in T lymphocytes and macrophages and secondly the immune suppression of T lymphocyte responses (Strayer, 1992;Jeklova et al, 2008) and widespread destruction of lymphoid tissue (Hurst, 1937a;. At least five myxoma virus genes are essential for replication in T lymphocytes and macrophages (M002, M004, M005, M011, M013) (Stanford et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the actual impact of the two diseases under natural conditions will depend on the seasonal timing of disease introduction, as a later introduction of MYXV into a host population will dampen the positive effect on disease severity and population extirpation in relation to delayed susceptibility to RHDV. Some of the impact of myxomatosis on RHD severity, however, is likely underestimated in our modelling, because we did not take immunosuppressive characteristics of MYXV [56] into account. With a relatively low impact of myxomatosis on rabbit populations, RHDV infection and disease delay may become an important driver of disease severity and population extirpation.…”
Section: Discussionmentioning
confidence: 99%